Population Density: An Underlying Mechanism Between Road Transportation and Environmental Quality - Din, Ashraf Ud; Ming, Jian; Vega-Muñoz, Alejandro; Salazar Sepúlveda, Guido; Contreras-Barraza, Nicolás (Frontiers in Environmental Science, 2022)
The mounting degradation in the environment quality specifically from transport industry is a big threat and challenge for the sustainable development. The transport sector’s emission has gained the researchers attention on climate change and transportation because of its increasing share in global emission. This study, thus, aims to analyze the links among road infrastructure, road transport energy consumption and environment quality with the moderating role of population density. The study has used a dataset of five countries of South Asia for 1971-2014. The study finds positive effect of road infrastructure, road density, energy intensity and road transport energy consumption on transport generated emissions which indicates that the road transportation is harmful for the environment quality. Our results confirm the significant moderating role of population density in strengthening the relations of road infrastructure, road transport energy consumption and environment quality. It is concluded that population density works as a bridge between the road infrastructure, road transport energy consumption and environment quality which helps to capture a strong impact of road transportation. We offer the planners of road transportation with a novel and practical approach to examine complex secular population density changes policy in the growing countries to analyze the environment quality.